Manual of medical therapeutics (Little, Brown, 1995)
Organized by body system, this manual is designed to provide busy clinicians with the right information they need for effective treatment decisions. The focus of the book is therapy; diagnostic and pathophysiologic information appears only when useful in recognizing or treating a particular problem. The book's outline format makes it easy to locate precisely the information sought. Current references are also embedded within the text for additional study purposes.